The Appeal and Applicability of ICT Study Materials: the Viewpoint of Generation-Z Pre-Service Teachers - Bratina, Tomaž (Revija za elementarno izobraževanje, 2017)
Effective contemporary teaching is closely connected to the inclusion of ICT, which comprises technological tools and the preparation and distribution of multimedia learning content. Therefore, one of the objectives of pre-service teacher education is to produce a technologically competent teacher. For this reason, the study programme includes a range of learning content where pre-service teachers engage in practical work in order to learn about the uses of ICT, tools and procedures for the production and distribution of multimedia learning content. Current generations of pre-service teachers are considered as belonging to Generation Z, or digital natives, and we can consequently expect experience, greater interest in studying the material and motivation to use ICT in their work. After the conclusion of the ICT in Education course, a study was prepared focusing on the learning materials that pre-service teachers find interesting, how they assess the applicability and transferability of this material and on the assessment of their own qualification for preparing multimedia learning materials. The results have shown that contemporary generations are familiar with working with ICT; however, they lack the experience and knowledge for using programs and tools. They want more knowledge and practical work in preparing multimedia learning material and in its distribution. The possibility of distributing multimedia learning content has resulted in a notable interest in working with Moodle, which is evident from the comparison of results from this year’s generation and those from two years ago. Students believe that the syllabus provided is interesting and useful. The acquired knowledge will be useful in the production of future learning materials and for work in other courses. The findings of the study will be used in the updating and preparation of future syllabi.
Keywords: ICT; pre-service teachers; Generation Z; study materials; digital competences; ICT in education